Establishment of Satellite Schools is it a Blessing or it's a Curse. A Case of Binga District in Zimbabwe (Global Journal of Human-Social Science, 2021)
The government of Zimbabwe played an important role in the creation of the satellite schools in far-flung areas in post-colonial era. The main thrust of the article is to unravel the stimulus or impetus behind the establishment of the satellite schools in rural areas. Using mixed research design, 130 participants were interviewed during the survey in order to delve more information about the motives behind the establishment of satellite schools. Though most of the communities considered the move as a blessing towards bridging the gap of the rural pupils who could travel long distances of more than 8 Kilometres per day to and from school. Ramshackle infrastructure, laughable resources and school drop outs were major challenges facing satellite schools in Binga. With regard to ameliorate the situation, participants proposed various strategies which includes community participation, donor aid and government intervention and slacked educational policies just to mention a few. This study established that, blessings were mingled with ignominy, discomfitures and discomposure in Zimbabwe's rural satellite schools.
Keywords: satellite schools; development and community